Comparative analysis of the folding dynamics and kinetics of an engineered knotted protein and its variants derived from HP0242 of Helicobacter pylori. (9th September 2015) - Wang, Liang-Wei; Liu, Yu-Nan; Lyu, Ping-Chiang; Jackson, Sophie E; Hsu, Shang-Te Danny
Abstract Understanding the mechanism by which a polypeptide chain thread itself spontaneously to attain a knotted conformation has been a major challenge in the field of protein folding. HP0242 is a homodimeric protein from Helicobacter pylori with intertwined helices to form a unique pseudo-knotted folding topology. A tandem HP0242 repeat has been constructed to become the first engineered trefoil-knotted protein. Its small size renders it a model system for computational analyses to examine its folding and knotting pathways. Here we report a multi-parametric study on the folding stability and kinetics of a library of HP0242 variants, including the trefoil-knotted tandem HP0242 repeat, using far-UV circular dichroism and fluorescence spectroscopy. Equilibrium chemical denaturation of HP0242 variants shows the presence of highly populated dimeric and structurally heterogeneous folding intermediates. Such equilibrium folding intermediates retain significant amount of helical structures except those at the N- and C-terminal regions in the native structure. Stopped-flow fluorescence measurements of HP0242 variants show that spontaneous refolding into knotted structures can be achieved within seconds, which is several orders of magnitude faster than previously observed for other knotted proteins. Nevertheless, the complex chevron plots indicate that HP0242 variants are prone to misfold into kinetic traps, leading to severely rolled-over refolding arms. The experimental observations are in general agreement with the previously reported molecular dynamics simulations. Based on our results, kinetic folding pathways are proposed to qualitatively describe the complex folding processes of HP0242 variants.